2018
DOI: 10.1002/glia.23546
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin receptor agonist reduces perinatal brain damage by targeting microglia

Abstract: Prematurity and fetal growth restriction (FGR) are frequent conditions associated with adverse neurocognitive outcomes. We have previously identified early deregulation of genes controlling neuroinflammation as a putative mechanism linking FGR and abnormal trajectory of the developing brain. While the oxytocin system was also found to be impaired following adverse perinatal events, its role in the modulation of neuroinflammation in the developing brain is still unknown. We used a double‐hit rat model of perina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 56 publications
2
61
0
1
Order By: Relevance
“…A combination of perinatal brain injury induced by a gestational low-protein diet and postnatal injections of interleukin-1β (IL-1β), caused an upregulation of inflammation-related gene sets and an increase in microglial cell number in cortical white matter at P4. Cultured microglial cells from P2 low-protein-diet animals displayed a more amoeboid morphology and released higher concentrations of several pro-inflammatory cytokines with respect to controls [45].…”
Section: Prenatal Environmental Agents and Infectionmentioning
confidence: 88%
See 1 more Smart Citation
“…A combination of perinatal brain injury induced by a gestational low-protein diet and postnatal injections of interleukin-1β (IL-1β), caused an upregulation of inflammation-related gene sets and an increase in microglial cell number in cortical white matter at P4. Cultured microglial cells from P2 low-protein-diet animals displayed a more amoeboid morphology and released higher concentrations of several pro-inflammatory cytokines with respect to controls [45].…”
Section: Prenatal Environmental Agents and Infectionmentioning
confidence: 88%
“…Recently, Amini-Khoei et al (2017) demonstrated that intracerebral administration of OXT reduced pro-inflammatory gene expression related to microglia activity, including TNF-α, IL-1β, and TLR4, in the HIP of adult animals exposed to MS [128]. In a double-hit model using a low-protein diet to induce perinatal brain damage followed by postnatal injections of IL-1β during early life, the accompanying administration of the OXT receptor agonist carbetocin was found to prevent microglial activation and reduce the effects of the low-protein diet and IL-1β injections on genes associated with microglial activation throughout the brain [45].…”
Section: Early Preventative Interventionsmentioning
confidence: 95%
“…We developed a preclinical model of perinatal brain injury associated with IUGR by combining gestational LPD (29) with IL-1b injection of the pups. Animals exposed to this double-hit insult showed neuro-inflammation and microglial hyperactivity, detected not only in vivo but also in cultured microglia sorted from the neonatal brain (25,30).…”
Section: Discussionmentioning
confidence: 99%
“…Microglial cells were isolated from CTRL and LPD/IL-1β animals at P4 and P7 and cultured as previously reported (25). CTRL microglial cells were treated with LY 379268 (0.…”
Section: Primary Microglial Cell Culture: Real-time Qpcr and Morpholomentioning
confidence: 99%
“…Oestrogen and oxytocin levels change in sires . Using different lesion techniques, these hormones have been investigated as possible neuroprotective agents (oestrogen and oxytocinmediated neuroprotection). As a result of the complexity of parental adaptations occurring in the male, more experiments are needed to address the possibility that these hormones, differentially regulated in sires, have a role in the neuroprotective effects observed in the present study.…”
Section: Discussionmentioning
confidence: 99%